The effect of rootgap distance and polarity on deffects in SMAW welding procedure - Nurfauziah, Ade; Nurlela, Nurlela; Hidayat, Topik; Manullang, Wahyu Efendi; Wibisono putra, Ananda Yhuto (Journal of Welding Technology, 2023)
SMAW (Shielded Metal Arc Welding) welding has wide applications in the industrial world. To master welding technology, it is necessary to carry out further research on the effect of gaps on the microstructure after experiencing welding. Welding is a process of joining metalsby heating process, because of that, the process can change the basic properties of the base material. In this study, the material used was ASTM A36 carbon steel. That material was weldedby many variables that have been determined and the limitations of the problem during the study. The required specimen welding results are 6 pieces. There are three kindsof variables in this research; theywere independent variables, namely the Rootgap distance and polarity on the electrodes of the SMAW welding machine, using two types of polarity, namely (DCEN) and (DCEP). The dependent variables in this study were defects in the translucency of SMAW welding results obtained bySolvent Penetrant Testing method. The control variables in this study were welding current 90A, Voltage 21V, Electrode AWS A5.1 E6013 with SMAW welding process and Butt-joint welding type. The welding joint was a V-groovewith 30º of bevel angle and 2mm of root face. The study results showed that the welding translucency is affected by polarity and rootgap distance, where the DCEN polarity showed better translucent welding results than welding with DCEP polarity, even though it was still not in accordance with the standard.